Effects of training intervention on non-ergonomic positions among video display terminals (VDT) users. - Mirmohammadi, Seyed Jalil; Mehrparvar, Amir Houshang; Olia, Mohammad Bagher; Mirmohammadi, Monirolsadat (Work, 2012)
Objective: Substantial evidence shows an association between musculoskeletal disorders (MSDs) and certain work-related physical factors. One of the jobs with known ergonomic hazards is working with video display terminals (VDTs). Redesign, ergonomic improvements, and education have generally been recommended as solutions for the prevention of musculoskeletal disorders. We designed this study to assess the effects of ergonomic training on the working postures of VDT users. Methods: In an intervention study, we assessed the impact of ergonomic training on the ergonomic hazards and work postures in employees working with VDTs. Participants and their workstations were assessed by Rapid Upper Limb Assessment (RULA) method before and after training. Participants: 70 employees of an office, working with a VDT more than four hours per day entered the study. Results: The greatest compliance with OSHA workstation recommendations was seen with the monitor (21.4% of cases) and the least compliance with the one was the chair (10.0%). Mean RULA score before and after intervention were 5.90, and 5.07, respectively, and the difference was statistically significant (p < 0.001). Conclusions: It can be concluded from this study that training office ergonomics to the VDT users, even without changing work place components can significantly improve VDT users' behavior and ability to properly fit a workstation to him/herself.